Vigorous Neuronal Differentiation of Amplified and Grafted Basic Fibroblast Growth Factor-Responsive Neurospheres Derived from Neuroepithelial Stem Cells - Motoyuki Yamada; Koichi Uchida M.D.; Takuro Hayashi; Yutaka Mine; Takeshi Kawase (Cell Transplantation, 2004)
Neuroepithelial stem cells (NESCs) have emerged as a possible donor material aimed at neural transplantation for the repair of damaged neural circuitry, particularly because of their propensity to differentiate into neurons. We previously ascertained in vitro that NESCs derived from rat early embryos could be amplified in culture containing basic fibroblast growth factors (bFGF), and that neurospheres grown for 7 days in the culture had a strong tendency to differentiate into neurons. In this report, we analyze immunohistochemically the biological nature of bFGF-responsive neurospheres derived from NESCs. We first succeeded in amplifying the number of NESCs from the mesencephalic neural plate of embryonic day 10 Wistar rats with the addition of bFGF. Grown neurospheres were labeled with bromodeoxyuridine (BrdU) in vitro and were stereotactically transplanted into the right striatum of the normal adult Wistar rat. Two weeks after transplantation, a viable graft in the host brain was observed. While many BrdU/Hu double positive cells were seen in the graft, and a few BrdU/nestin double positive cells were also seen, no BrdU/GFAP double positive cells could be identified. These results suggested that bFGF-responsive neurospheres derived from NESCs demonstrated a propensity to differentiate into neurons in the adult brain environment. Furthermore, following in vitro amplification of the original stem cell number with bFGF, the grown neurospheres preserved their propensity to differentiate vigorously into neurons. NESCs are thus suggested as a feasible candidate for intracerebral grafting donor materials aimed at reconstruction of damaged neural circuits.